Revised temporal and morphostratigraphic context for Clark Quarry: A late-Pleistocene, fluvially-reworked, Atlantic coast backbarrier deposit. (15th May 2022) - Seminack, Christopher T.; Thornburg, Jesse D.; Mead, Alfred J.; Mead, Heidi F.; Hadden, Carla S.; Cherkinsky, Alexander; Nelson, Michelle S.; Patterson, David B.
Abstract: Sediments along the Atlantic Coastal Plain (ACP) of North America have been the focus of numerous paleontological investigations and yielded a diverse array of vertebrate remains; yet the depositional environments associated with their preservation are poorly understood. In this study, we present a multidisciplinary analysis of the depositional environment at Clark Quarry, a late-Pleistocene, fossil-rich locality located within the ACP in Georgia, USA. Clark Quarry is currently positioned 15 km west of the Atlantic Ocean coast and lies within the Princess Anne Terrace, a 100–80 ka paleobarrier-island complex. Fossil-bearing sediments at Clark Quarry are interpreted to have been deposited as a low-energy, fluvial environment that subsequently reworked low-lying terrain of the Princess Anne Terrace backbarrier. Interpretations of digital elevation models (DEM) and infrared stimulated luminescence (IRSL) ages on K-rich feldspar sand grains indicate that this region was an estuarine zone backing (i.e., westward) the Princess Anne paleobarrier island that was subsequently reworked by fluvial activity 68–52 ka. These new interpretations, paired with additional radiocarbon ages from fossil carbonates and overlying soil horizons, indicate that radiocarbon samples may have been influenced by isotopic exchange and should be interpreted as minimum age estimates. Additionally, ground-penetrating radar (GPR) surveys in conjunction with DEM analysis may have captured the subsurface signature of a meandering fluvial system transitioning to a braided style, emphasizing the dynamic nature of this depositional environment. Non-preferential orientation of excavated long bones suggests multidirectional paleoflow, further suggesting a braided stream influence. When considered in conjunction, these data: 1) indicate that Clark Quarry represents a spatially and temporally resolved window into the late-Pleistocene ecosystem in southeastern North America, and 2) suggest that existing radiocarbon data from late-Pleistocene ACP localities should be considered with caution. Highlights: Sediments at Clark Quarry were likely deposited by a fluvial environment. Sediment deposition at Clark Quarry took place 68.23–52.24 ka. The fluvial style likely switched from a meandering to a braided stream. 14 C dates in this study are younger than OSL dates due to isotopic exchange.